Protective effects of Ceratonia siliqua extract on protamine gene expression, testicular function, and testicular histology in doxorubicin-treated adult rats: An experimental study - Hengameh Mehdi Khani; Mehrdad Shariati; Mohsen Forouzanfar; Seyed Ebrahim Hosseini (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Spermatogenesis is a complex process that takes place under the influence of many different genes. Objective: The aim of this study was to investigate the possible effects of Ceratonia siliqua hydroalcoholic extract (CSHAE) on protamine gene expression, testicular function, and testicular histology in doxorubicin-treated rats. Materials and Methods: 56 adult male rats with a age range of 2.5 to 3 months (210 ± 10 gr) were divided into seven groups (n = 8/each). A) Control group was left untreated; B) Sham group received 0.3 ml distilled water intraperitoneally, C) Negative control group received 3 mg/kg doxorubicin, intraperitoneally once a week for 28 days; and D) Positive control group received 600 mg/kg of CSHAE orally for 48 days; E, F, G) the experimental groups 1, 2, and 3 received 150, 300, and 600 mg/kg of CSHAE respectively orally, for 48 days, as well as 3 mg/kg doxorubicin once a week for 28 days. Hematoxylin-eosin staining was used in the histological study of testes, and enzyme-linked immunosorbent assay method was used in measuring serum levels of testosterone. Protamine gene expression was determined by real-Time PCR method. Results: The mean body weight, testicular weight, testicular volume, testosterone level (p = 0.022), the count of Leydig, spermatogonia, spermatocyte, and spermatid cells, as well as protamine gene expression (p = 0.008) were significantly increased in the experimental group 2 compared to the negative control group. The regeneration of testicular tissue was observed in the experimental group 2. Conclusion: CSHAE has protective effect on doxorubicin-induced testicular injuries.